One Episode of Self-Resolving Plasmodium yoelii Infection Transiently Exacerbates Chronic Mycobacterium tuberculosis Infection - Blank, Jannike; Eggers, Lars; Behrends, Jochen; Jacobs, Thomas; Schneider, Bianca E. (Frontiers in Microbiology, 2016)
Malaria and tuberculosis (Tb) are two of the main causes of death from infectious diseases globally. The pathogenic agents, Plasmodium parasites and Mycobacterium tuberculosis (Mtb), are co-endemic in many regions in the world however compared to other co-infections like HIV/Tb or helminth/Tb, malaria/Tb has been given less attention both in clinical and immunological studies. Due to the lack of sufficient human data, the impact of malaria on Tb and vice versa is difficult to estimate but co-infections are likely to occur very frequently. Due to its immunomodulatory properties malaria might be an underestimated risk factor for latent or active Tb patients particularly in high-endemic malaria settings were people experience reinfections very frequently. In the present study, we used the non-lethal strain of Plasmodium yoelii to investigate how one episode of self-resolving malaria impact on a chronic Mtb infection. P. yoelii co-infection resulted in exacerbation of Tb disease as demonstrated by increased pathology and cellular infiltration of the lungs which coincided with elevated levels of pro- and anti-inflammatory mediators. T cell responses were not impaired in co-infected mice but enhanced and likely contributed to increased cytokine production. We found a slight but statistically significant increase in Mtb burden in co-infected animals and increased lung CFU was positively correlated with elevated levels of TNFbut not IL-10. Infection with P. yoelii induced the recruitment of a CD11c+ population into lungs and spleens of Mtb infected mice. CD11c+ cells isolated from P. yoelii infected spleens promoted survival and growth of Mtb in vitro. 170 days after P. yoelii infection changes in immunopathology and cellular immune responses were no longer apparent while Mtb numbers were still slightly higher in lungs, but not in spleens of co-infected mice. In conclusion, one episode of P. yoelii co-infection transiently exacerbated disease severity but had no long-term consequences on disease progression and survival of Mtb infected mice.